Effectiveness of social media marketing in social awarness campaign / Mohd Khairul Anwar Baharin - Baharin, Mohd Khairul Anwar (2015)
A social media and internet is emerging where media cultures are changing young people's lives in both the private and public behaviour. Many people's lives today by internet where people used laptops, websites, mobile phones, computers and iPods. Since the introduction of Internet technologies, the interactive elements that are offered to the user had turned the Internet into a modem social platform that involved mass participation. It has evolved into this new form of social media that can transmit multimedia content and give the interaction between senders and receivers or between content providers and the audiences. This media has led to the formation of a new form of communication that has given mass commnunication and interpersonal communication into new interactivities such as chat groups, virtual groups in workplaces, and online communities. Internet and social media helps the user to overcome the technical obstacles that we see the way earlier and making the Internet an instrument for and by the mass user. Cyberspace now becomes a new playground and online interaction where people get together and form groups based on interest with the use of social networking and virtual world sites. Millions are logging in, joining up, and participating. It has become more fun, interactive, and lives with elements of video, audio, and digital animation offered by this new media.